Animal Models for Preclinical Development of Allogeneic Hematopoietic Cell Transplantation. (12th July 2018) - Graves, Scott S; Parker, Maura H; Storb, Rainer
Abstract: Since its inception in the 1950s, hematopoietic cell transplantation (HCT) has become a highly effective clinical treatment for malignant and nonmalignant hematological disorders. This milestone in cancer therapy was only possible through decades of intensive research using murine and canine animal models that overcame what appeared in the early days to be insurmountable obstacles. Conditioning protocols for tumor ablation and immunosuppression of the recipient using irradiation and chemotherapeutic drugs were developed in mouse and dog models as well as postgrafting immunosuppression methods essential for dependable donor cell engraftment. The random-bred canine was particularly important in defining the role of histocompatibility barriers and the development of the nonmyeloablative transplantation procedure, making HCT available to elderly patients with comorbidities. Two complications limit the success of HCT: disease relapse and graft versus host disease. Studies in both mice and dogs have made significant progress toward reducing and to some degree eliminating patient morbidity and mortality associated with both disease relapse and graft versus host disease. However, more investigation is needed to make HCT more effective, safer, and available as a treatment modality for other non-life-threatening diseases such as autoimmune disorders. Here, we focus our review on the contributions made by both the murine and canine models for the successful past and future development of HCT.